Correlation between childhood participation in physical activity and young adulthood participation in physical activity in NTU students - Pang, Li Yuan (2018)
Sedentary lifestyle increases the risk of chronic illnesses. Coupled with ageing population, the strain on healthcare has been increasing. There is an increasing focus and interest in physical activity (PA). However, there is still a lack of PA participation amongst Singaporeans. The government is looking into preventive measures which include living a healthy and active lifestyle to keep these chronic illnesses at bay. PA participation prior to adulthood is thought to have an effect on adulthood PA participation. This research aims to find out if there is positive correlation between childhood physical activity (PA) and young adulthood PA participation. Thereby, bringing attention to importance of cultivating the habit of PA participation from young. This study would be useful to physical education policy makers, parents and young individuals. Hardcopy survey were used to gather responses from 50 participants who are currently regularly participating in PA. Data from 21 females and 29 males were analyzed using Statistical Package for the Social Sciences (SPSS) software. Results showed that almost all participants had prior PA participation. The positive correlation between childhood participation in PA and young adulthood PA participation was of moderate effect size but not significant. Interestingly, there is a significant strong positive correlation between childhood PA participation and adolescence PA participation, for both competitive and recreational PA. In conclusion, though positive correlation between childhood participation in PA and young adulthood PA participation lacks significance, participation in PA since young is encouraged.